An Analysis of FEE_HELP in the Vocational Education and Training Sector - Ryan, C; Chapman, B; Rodrigues, M (My University, 2008)
The public vocational education and training (VET) system is now one of the few areas in Australia’s tertiary education system where students are required to pay up-front fees without access to loan assistance. These arrangements may lead to sub-optimal educational outcomes to the extent that prospective students reject a VET education on the basis of short-term financial constraints. In this paper we analyse some of the important issues related to the adoption of FEE-HELP (a 2005 Federal Government financial instrument based on the Higher Education Contribution Scheme ((HECS)). It is argued that income contingent loans of this kind are associated with the advantages of both default-protection and consumption smoothing. Using data from the first three waves of the Household Income and Labour Dynamics in Australia (HILDA) survey, we examine various empirical issues associated with the adoption of FEE-HELP in VET, including the extent of private salary returns to VET qualifications. As well, we explore issues related to the public subsidies inherent in the adoption of FEE-HELP in VET, and illustrate the time periods involved in loan repayments for various assumptions concerning the size of the charge and the future income of VET graduates. Administrative issues are considered, as are the implications for the Commonwealth Government with respect to potential subsidies associated with the design parameters.
Centre for Economic Policy Research, the Australian National University, Discussion Paper
Keywords: Education and Training -- Costs; Education and Training; Education and Training -- Training; Learning, education and training; Learning, education and training